Firing costs and the business cycle: Policy implications in light of the financial crisis - Alessio J. G. Brown; Christian Merkl; Wolfgang Lechthaler (The crisis and beyond, 2009)
This lecture is a tour d'horizon of the financial crisis aimed at extracting lessons for future financial regulation. It combines normative recommendations based on conventional welfare economics with positive assessments of the kind of measures likely to be adopted based on political economy considerations.
Keywords: 330; Konjunktur; Kündigung; Arbeitsmobilität; Kosten; Währungsunion; Arbeitnehmerschutz